SANCTIONS OF CASTRATED FOR CHILDREN VIATORS REVIEWING FROM HUMAN RIGHTS - Ajie Prasetya; Aris Prio Agus Santoso; Yulia Emma Sigalingging (International Journal of Law and Legal Ethics, 2022)
The problem of sexual violence is difficult to overcome and almost impossible to eliminate, the victims are mostly children so that the castration sentence is sought to be an additional sanction in addition to the main punishment. The castration sanction is a polemic because the castration provision can affect human rights. The purpose of this research is to what is the criminal law policy for imposing castration sanctions anda how is castration sanctioned in terms of human rights. The research method is normative with the approach used is a conceptual approach, through secondary data collection. The researcher chose the normative approach because of time and cost limitations if this research was conducted empirically, considering that finding respondents who had been castrated was also not an easy matter. The type of research design used is Descriptive Design. Data collection in this research is by literature study. Data analysis in this study uses qualitative analysis techniques, namely to find out the problems that arise. Based on the results of the discussion, it was found the fact that the application of sanctions as outlined in Government Regulation in Lieu of Law Number 1 Year 2016 is expected to provide a deterrent effect for pedophile perpetrators by carrying out imprisonment and castration. However, it must be done after going through coordination with the Ministry of Health, because it is feared that it will have a bad impact on health. In addition, there is also no research that proves that perpetrators of sexual violence after castration can have offspring. Some cases were castrated and some were not. The castration sanction is only carried out in cases of obscenity which are classified as severe so that the judge gives a different decision. The castration sanction is an act that violates human rights, particularly related to reproductive health.